Beyond Montessori: comparative and diachronic reflections on the theme of differences - Nuti, Gianni; Filippa, Manuela (Studi sulla Formazione/Open Journal of Education, 2021)
In the present paper, we aim to investigate the theoretical foundations and consequent actions that moved Maria Montessori to explore, as a pioneer, the theme of individual differences. More specifically, the objective is to analyse the interconnection between the theme of differences which, in Maria Montessori’s work, features as context and pretext for informed pedagogical action steered towards inclusion in formal and non-formal educational contexts, revising the classic paradigms of intervention, in the light of the most recent interdisciplinary scientific discoveries.